Allocation of risk capital based on iso-entropic coherent risk measure - Chengli Zheng; Yan Chen (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The potential of diversified portfolio leads to the risk capital allocation problem. There are many kinds of methods or rules to allocate risk capital. However, they have flaws, such as non-continuity, unfairness. In order to get a better method, we propose a new risk measure to be the base of risk capital allocation rule. Design/methodology/approach: We proposed two kinds of allocation methods: one is marginal risk contribution based on iso-entropic coherent risk measure(IE), the other one is to combine the minimal excess allocation(EBA) principle and IE into risk capital allocation. The iso-entropic coherent risk measure has many advantages over others; it is continuous and more powerful in distinguishing risks, consistent with higher-order stochastic dominances than other risk measures. And EBA is consistent with the amount of risk, which means fairness for risk capital allocation. Findings: Through cases, simulations and empirical application, it shows that these two allocation rules satisfy some good properties, can be more efficient, more precise and fairer. And the EBA based on IE may be the better one. Research limitations/implications: However, there are some problems still open. One is how to treat the negative value of allocation. Second is that the consistence between the allocated risk capital and the amount of the risk needs to be studied further. Originality/value: A good risk measure is very important for risk capital allocation. We proposed two methods to deal with risk capital allocation based on a new coherent risk measure called iso-entropic risk measure, which is smooth and consistent with higher-order stochastic dominance and has higher resolution of risk. It shows that the risk capital allocation rules based on iso-entropic risk measure are better than the other rules.
Keywords: 650; risk capital allocation; marginal risk contribution; minimal excess principle; iso-entropic coherent risk measure